(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background and objective: Mental health and patient safety is necessary in hospitals and health care settings .Nurses should know perception of patient safety in their field so patient safety includes everyone in all aspects of health care. Nurses understood patient safety as taking care of patient with psychiatric problems and maintain health through good treatment and respecting self-determination and avoiding coercion. The aims of this study were to assess the patient safety in Hawler psychiatry hospital/Erbil city and find out the association between demographic characteristics of the nurses and their roles regarding patient safety. Methods: This cross-sectional study was conducted on 33 nurses in Hawler psychiatry hospital/Erbil city. A questionnaire was designed for the purpose of the study. Data were collected through interview with nurses. Frequency and Chi-square test was used for data analysis. Results: 45.5 % of participants were in the age group 38-50 years old. Majority (69.7%) of them were male, 78.8 % from urban areas, 42.4 % of them were Preparatory School of nursing graduated, had income was somehow sufficient (78.8 %), married (90.9%). The overall nurse practice regarding patient safety was 81.8 was moderate, the overall patient safety related to environment of psychiatric hospital as estimated 84.8 % was poor. Regarding overall nursing practice related to patient safety and socio-demographic data of nurses, there were statistically significant differences between level of education of nurses (p-value=0.007) and level of economic status of nurses (p-value= 0.005) with patient safety. Conclusion: The overall practice regarding patient safety was moderate, and the overall nurse practice regarding patient safety was poor in Hawler psychiatric hospital ,so continuous education the nurses regarding patients’ safety and provide all equipment’s that needed for provide proper environment are necessary .